PHYTOCHEMICAL EVALUATION OF Plumbago Indica L. ROOT EXTRACTS - Hemant Bhatia; Dharmendra Ahuja (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Aim: The active ingredient of Plumbago indica L., Plumbagin, has long been associated with a number of pharmacological actions. For the purpose to determine phytochemical evaluation of Plumbago indica L. root extracts Methods: For the purpose to determine the crude drug’s purity, it underwent pharmacognostic assessment and standardization. Later that, the extract of plants underwent qualitative phytochemical analysis, and its total phenolic and flavonoid content was quantified. Extract isolation with thin layer Chromatography, Column Chromatography, UV-visible Spectroscopy, FT-IR, NMR, and Mass Spectroscopy Results: Following the extraction of Plumbago indica L. root powder, the methanolic, ethyl acetate, and chloroform extract contained the highest total flavonoid content, which was determined using rutin as a standard. The total phenolic content of the extract was also measured in relation to gallic acid confirming the primary functional group present in the sample by isolating and characterizing the extraction using Thin Layer Chromatography (TLC), Column Chromatography (CLC), UV-visible Spectroscopy (UV-VIS), FT-IR, NMR, and Mass Spectroscopy Conclusion: The study project’s outcomes indicated that Plumbago indica L., roots are rich in phytochemicals, and the presence of Plumbagin is the main source of Plumbago indica L significant several activities. The identity and purity of the compound was confirmed by Thin layer Chromatography, Column Chromatography, UV-visible Spectroscopy, FT-IR, NMR, Mass Spectroscopy. These data strongly support the possible utility of these extracts in disease prevention and treatment. Further the purpose of this study is to formulate (Herbosome) and investigate the effects of Plumbago indica L root extract and Plumbagin on hepatic maliganacy